Phenotypic and genetic trends of reproductive post-weaning growth: Cow productive traits in Kenyan Boran cattle - Okeyo Mwai, Ally; Mosi, R.O.; Rege, J.E.O.; Shibre, M. (South African Society of Animal Science, 1996)
Phenotypeic and genetic trends of calving interval (CI), nine months corrected weaning weight (9MOWT) and calf weight, weaned/cow/year (cow index), were estimated on data from three ranches (Mogwooni, Galana and Oljorai) located in semi arid areas of Kenya. The number of records per herd varied between 1200 and 9303 and covered periods of between 10 and 30 years. A mixed animal model was used to estimate the phenotypic, genetic and environmental components which were then averaged and weighted for each animal record within year of entry. Results of the data analysis on phenotypic changes in CI, corresponding annual phenotypic changes for 9MOWT, respective annual changes for the three ranches, annual phenotypic changes in cow index and annual genotypic changes are presented. With the exception of Mogwooni, the phenotypic trends were negative for CI but positive for 9MOWT and Cow Index. Overall environmental changes in CI were negative but insignificant on Galana and Oljorai (desirable), on Mogwooni environmental changes in CI were positive but insignificant (undesirable). Positive but insignificant overall phenotypic genetic changes in 9MOWT were negative but insignificant, while the corresponding environmental changes were positive. For the Cow Index there were significant positive environmental changes in Mogwooni and Oljorai only, but insignificant in Galana. Corresponding positive genetic changes were observed in Mogwooni and Oljorai but not in Galana herds. The implications of the results are discussed.